Virtual teams in Malaysia: A qualitative investigation in Multimedia Super Corridor status companies - Aripin, Norizah; Mustafa, Hasrina; Hussein, Adnan (Universiti Tun Hussein Onn Malaysia, 2010)
The proliferation of various communication technologies such as e-mail, Instant Messaging, video conferencing audio conferencing and others in organizations today has led to the development of a special group called virtual team. A virtual team is defined as a group of people who interact through interdependent tasks by common purpose and work across space and organizational boundaries with links strengthened by webs of communication technologies. A virtual team works with its members scattered across regions with time and cultural differences.These factors pose a challenge to team members in creating and developing a dynamic and productive team.Thus, the aim of this study is to understand virtual teams and its working environment in MSC status organizations.The study uses qualitative method that is indepth interview with semi-structured and open ended questions.Interviews involving three staffs (project manager, leader and employee) from three multinational organizations such as Motorola, software development and hardware design.The interviews were recorded,transcribed and analyzed according to the thematic analysis.Study results show that work in virtual teams involving team members scattered or geographically dispersed team, the use of communication technologies and team relationship.In addition, the study also found that factors team culture, time zone differences and language contribute to virtual team working environment.